Melanin/PEDOT:PSS organic synaptic transistors: a step towards sustainable neuromorphic applications - Natan L Nozella; Guilherme S Selmi; Nayrim B Guerra; Marcelo R Piton; Carlos F O Graeff; Rafael F de Oliveira (Neuromorphic Computing and Engineering)
Inspired by the functioning of the human brain, organic synaptic transistors represent a promising avenue for developing neuromorphic technologies. However, achieving sustainability while maintaining performance and functionality remains a critical challenge. Here, we report on an innovative strategy where synthetic melanin (Mel)—a natural pigment known for its improved ionic–electronic coupling, high volumetric capacitance, and environmentally friendly characteristics—is blended with benchmark poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) to fabricate synaptic transistors. Mel/PEDOT:PSS blends having different amounts of Mel have been systematically evaluated as semiconducting layer in organic electrochemical transistors. Our findings reveal that Mel incorporation at different concentrations enables tunable synaptic responses, such as enhanced memory retention and access to multiple memory states. These effects arise from the unique properties of Mel which modulate the charge density of PEDOT:PSS in a controlled manner. This approach demonstrates the potential for developing highly stable, multi-level memory materials for organic neuromorphic devices while addressing sustainability goals. We believe our strategy can open new avenues via the integration of natural and bio-inspired materials into organic semiconductors towards the development of sustainable neuromorphic technologies.